Levetiracetam Add-On Therapy for Rolandic and Other Benign Idiopathic Focal Epilepsies - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Effectiveness of levetiracetam (LEV) in treatment of typical benign rolandic epilepsy and variants of benign idiopathic focal epilepsies was studied in 32 children (mean age 10.6 years, range 4-14) by researchers at Epilepsy Centre for Children and Young People, Vogtareuth, Germany.